Narrativa Amazônicas: Representações do Mito do Boto nas Narrativas dos moradores antigos da Comunidade da Missão. - Fonseca, Thaila Bastos da (2019)
Amazonian narratives are creations and elaborations of the human imagination, which reveal historical elements that need to be registered and analyzed within an Amazonian context. In this sense, the present work aims, above all, to highlight the culture of oral tradition within an interdisciplinary perspective in the Mission Community, since when reporting past events, people create a whole historical, social and cultural framework of the place where they live. These elements are essential to contribute to the historical and identity construction of this location. The research presents a qualitative approach and was based on the Amazonian narratives about boto, in order to understand the vestiges of the colonial encounter between the peoples of the Amazon and the white man; the erotic and virile category of this myth as a mythological configuration as an oppressor of women victims of patriarchy. The problem emerged because the history of the colonial period in this location is still presented through the perspective of the colonizer, since there are few written records of our ancestors. For theoretical development we selected authors such as Franz Boas (2005), Laraia (2005), Todorov (2006), Hall (1996), Bauman (1999) and Santos (2010). Thus, this work contributed to the strengthening of the culture of oral tradition in the Mission Community and, above all, we proved that the stories of enchantment remain alive in the memories of those who narrated them, revealing historiographic elements that made it possible to understand the consequences of the colonial encounter, the construction of patriarchy in our society and the violation of women victims of male domination.